A case series study of the neurophysiological effects of altered states of mind during intense Islamic prayer. Issue 4 (December 2015) - Newberg, Andrew B.; Wintering, Nancy A.; Yaden, David B.; Waldman, Mark R.; Reddin, Janet; Alavi, Abass
Highlights: We present a case series of brain SPECT scans during intense Islamic prayer practices. Intense prayer practices were associated with specific patterns of brain activity. Intense prayer practices were found to have decreased frontal and parietal lobe activity. We discuss a variety of methodological issues and challenges that confront such research. Abstract: This paper presents a case series with preliminary data regarding the neurophysiological effects of specific prayer practices associated with the Islamic religion. Such practices, like other prayer practices, are likely associated with several coordinated cognitive activities and a complex pattern of brain physiology. However, there may also be changes specific to the goals of Islamic prayer which has, as its most fundamental concept, the surrendering of one's self to God. To evaluate Islamic prayer practices, we measured changes in cerebral blood flow (CBF) using single photon emission computed tomography (SPECT) in three Islamic individuals while practicing two different types of Islamic prayer. In this case series, intense Islamic prayer practices generally showed decreased CBF in the prefrontal cortex and related frontal lobe structures, and the parietal lobes. However, there were also several regions that differed between the two types of prayer practices including increased CBF in the caudate nucleus, insula, thalamus, and globus pallidus. These patterns also appear distinct from concentrative techniques in which an individual focuses on a particular idea or object. It is hypothesized that the changes in brain activity may be associated with feelings of "surrender" and "connectedness with God" described to be experienced during these intense Islamic prayer practices. Overall, these results suggest that several coordinated cognitive processes occur during intense Islamic prayer. Methodological issues and implications of the results are also discussed.